Quality of Life Outcomes Following Organ-Sparing SBRT in Previously Irradiated Recurrent Head and Neck Cancer - Gogineni, Emile; Zhang, Isabella; Rana, Zaker; Marrero, Mihaela; Gill, Gurtej; Sharma, Anurag; Riegel, Adam C.; Teckie, Sewit; Ghaly, Maged (Frontiers in Oncology, 2019)
Purpose: To present a retrospective analysis of the efficacy, toxicity, and quality of life (QoL) of patients treated with OARExtreme-sparing stereotactic body radiotherapy (SBRT) in previously-irradiated head and neck cancer. Materials/Methods: From 11/2012 to 7/2015, 60 patients with in-field recurrence of head and neck cancer underwent re-irradiation with SBRT. Retreatment sites included the aerodigestive tract (43%), lateral neck (22%) and skull base (35%). The median prior RT dose was 63.6Gy with a median time from prior irradiation of 16.5 months. The median volume treated was 61.0 cc. Patients were treated with 40 Gy in the definitive setting or 35 Gy in the post-operative setting in five fractions. Dose constraints to the OARExtreme were calculated with a BED calculator using an alpha/beta ratio of 3 to reduce the risk of late toxicities. QoL data was collected from patients at the time of consultation and at subsequent follow up appointments using the MD Anderson Dysphagia Inventory (MDADI) and Symptom Inventory (MDASI). Results: The 1-/2- year rates of local, regional and distant control and overall survival were 79/79%, 74/70%, 74/71% and 59/45%, respectively. Late grade 3 toxicities were seen in 3% in the group treated to the aerodigestive tract and 1% in the group treated to the skull base. No grade 4 or 5 toxicities were observed. Patients with skull base reirradiation maintained a stable QoL score after radiation treatment, while patients treated to the aerodigestive tract demonstrated a slight impairment associated with worsening dysphagia, compared to their pretreatment baseline. All groups experienced an increase in xerostomia. Conclusions: OARExtreme-sparing SBRT is able to achieve excellent tumor coverage while protecting the organs at highest risk of re-irradiation-related complications. The potential for lower toxicities and maintained quality of life with this treatment makes it a promising option for salvage of recurrent head and neck cancer.